Inhibitors of the oxidative phosphorylation pathway and their interaction with antibiotics in Mycobacteroides abscessus - Lim, Ting (Nanyang Technological University, 2024)
Mycobacteroides abscessus belongs to the family Mycobacteriaceae, along with highly pathogenic species Mycobacterium tuberculosis and Mycobacterium leprae, causative agents of tuberculosis and leprosy respectively. Since nontuberculous mycobacteria (NTM) are ubiquitous in the environment, human exposure is common, though severe disease is often limited to susceptible individuals such as the immunocompromised and those with underlying lung conditions. The rapidly growing M. abscessus is the most frequently isolated species from patients with NTM disease in Singapore. Due to its high levels of intrinsic drug resistance and increasing incidence of inducible resistance, treatment is largely ineffective or associated with relapse.